Pengaruh Fungsi Manajemen Terhadap Kinerja Karyawan PDAM Tirta Betuah Kabupaten Banyuasin - Suryanti; Riri Hanifa; Teguh Iman Santoso; Anton Kurniawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This study aims to analyze the influence of the management function (X) which includes Planning, Organizing, Actuating and Controlling on the performance of PDAM Tirta Betuah employees, Banyuasin Regency. This research is a quantitative descriptive with data acquisition through observation and questionnaire techniques. The sample used in this study were 30 respondents. The data collection technique in this study uses saturated sampling, which is a sampling technique when all members of the population are used as samples, another term for saturated samples is census. Meanwhile, the primary data collection used in this study was obtained from questionnaires distributed to respondents. Furthermore, the data that has been collected is analyzed with the help of the Smart PLS (Partial Least Squars) calculator version 3.0. From the results of the research used, the management function (Y) in PDAM Tirta Bertuah, Banyuasin Regency has a positive and significant effect on employee performance (X)